Night shift : [large type] a novel - Cook, Robin, 1940- (Thorndike Press large print core series., 2022)
"Colleagues turned spouses Dr. Laurie Montgomery and Dr. Jack Stapleton already have their plates full. The last thing they need is a murder. When Laurie's longtime friend Dr. Sue Passero dies in the hospital parking garage, an autopsy is required. With his curiosity sparked by the mystery around Sue's death, Jack sets out to investigate on-site at Manhattan Memorial Hospital even though it means defying the Office of Chief Medical Examiner's rules. What started out as an inquiry into Sue's tragic passing soon turns into a deadly chess game between Jack and the clever and deranged killer, who might just administer another lethal blow if Jack isn't careful."--